APPLICATION OF BREATHING DISORDERS TREATMENT PLANT WITH DRUG USING VISUAL BASIC 6.0 - Nano Handoko; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2006)
Any disorder or disease has a different treatment in both the treatment penyembuhanya chemical or medicinal plants, as well as respiratory disorders can be treated by using the wealth of nutritious edible or medicinal plants.  To help cure the problem then the author tries to make the application Respiratory Disorders Treatment With Medicinal Plants Using Visual Basic 6.0.  Discussion on Application of respiratory medication with medicinal plants is divided into four phases, namely, creating flowchart, menu structure, design input and output, and program development with Visual Basic 6.0